Constraints Analysis of Cauliflower Growers in Western Uttar Pradesh - Sunil Kumar, R.N. Yadav; Hari Nandan Prasad (Indian Journal of Extension Education, 2023)
The study was carried out during the year 2016-2017 in the cauliflower higher production area of Western Uttar Pradesh, Saharanpur region in the district of Saharanpur and Meerut region in district of Hapur over promising region for cauliflower cultivation. The number of two blocks selected for the study. Mujaffarabad block in district Saharanpur and Hapur block in district Hapur was purposively selected. The total sample size was of 160 cauliflower growers for the study. The result of the study depicted the majority of the respondents 51.25 per cent were belonging to lower middle age group ranging 30-45 years. Maximum 76.87 per cent respondents were belonged to other backward classes. The majority of the cauliflower growers were literate. The majority of 71.25 per cent the respondents were belonged to joint family system and interested for cauliflower growing. The maximum 61.87 per cent respondents of the cauliflower growers were having either medium size (5-8 members) of the family. The maximum 62.50 per cent respondents were having mixed houses. Only 80.00 per cent respondents were depending upon agriculture. The maximum 43.75 per cent cauliflower growers were having 01-02 ha of land holding small size. Unavailability of quality chemical at Govt. sale center, lack of knowledge about bio-fertilizers, fluctuation in the prices, lack of Govt. initiative in funding of loans and granting of subsidies problems in remote areas were all the most constraints. Highest majority of cauliflower growers were suggesting that availability of inputs at proper time Govt. sale centre and developed government tube well in every villages.